Evaluasi Kepuasan Pengguna Learning Management System Berbasis Web pada Pembelajaran Jarak Jauh: Evaluation of User Satisfaction with a Web-Based Learning Management System in Distance Learning - Azwar Azwar (WITECH: Jurnal Teknologi Rekayasa Komputer dan Jaringan, 2025)
This study aims to empirically examine the influence of system quality and information quality on user satisfaction with a web-based Learning Management System (LMS) in a distance learning environment. An explanatory research design was employed, and data were collected through an online questionnaire administered to 100 active users of KLC2. The study includes system quality and information quality as exogenous variables, and user satisfaction as the endogenous variable. Data were analyzed using SEM-PLS with SmartPLS 4 to assess path coefficients, t-statistics, and the significance of the structural relationships. The findings reveal that system quality exerts a positive and highly significant effect on user satisfaction (path coefficient = 0.965; t-statistic = 14.727; p < 0.001), indicating that improvements in the technical performance, usability, and reliability of the LMS strongly enhance user satisfaction. Conversely, information quality demonstrates a negative yet statistically significant effect on user satisfaction (path coefficient = −0.273; t-statistic = 2.897; p = 0.004). This result suggests a potential misalignment between the learning materials provided and the expectations or needs of learners, despite the materials being relatively easy to understand. These findings carry important implications for LMS administrators and system developers. Efforts to improve user satisfaction should prioritize enhancements to system quality, while ensuring that learning content is contextually relevant, appropriately designed, and responsive to users’ learning needs. Future research may expand the sampling frame, integrate mixed-method approaches to capture deeper insights, and incorporate more comprehensive indicators of information quality to strengthen explanatory power.